Implementasi Pembelajaran Augmented Reality di Sekolah Dasar: A Systematic Literature Review and Bibliometric Analysis - Mufidah, Zalfa; Darmayanti, Mela; Hendriani, Ani (Kayon Media, 2024)
Abstract: The use of AR technology in Elementary School learning is still lacking in terms of understanding and implementation. A systematic literature review is needed on the implementation of AR technology at the Elementary School. This study used bibliometric analysis method with applications Publish or Perish and VOSviewer. The use of AR technology has been implemented in Elementary Schools in several subjects including: Mathematics, Sciences, and English. The implementation of augmented reality in Elementary Schools has obstacle, it's unfamiliarity of using its technology. Hope in the future the implementation of AR in elementary schools will develop better and evenly distributed. Abstrak: Pemanfaatan teknologi AR dalam pembelajaran Sekolah Dasar masih kurang dari segi pemahaman dan implementasinya. Diperlukan kajian literatur yang sistematis mengenai penerapan teknologi AR di Sekolah Dasar. Penelitian ini menggunakan metode analisis bibliometrik dengan aplikasi Publish or Perish dan VOSviewer. Pemanfaatan teknologi AR telah diterapkan di Sekolah Dasar pada beberapa mata pelajaran antara lain: Matematika, IPA, dan Bahasa Inggris. Penerapan augmented reality di Sekolah Dasar mempunyai kendala yaitu belum terbiasa menggunakan teknologinya. Harapan kedepannya penerapan AR di sekolah dasar akan berkembang lebih baik dan merata